The degree of practicing the motivational leadership by the public school principals in the capital Amman governorate and its relationship to enhance the creativity culture among teachers from their point of view - Shamasneh, Jehan Mohamad Shawqi (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of practicing the motivational leadership by the public school principals in the capital Amman and its relationship to promoting a culture of creativity among teachers from their point of view. A descriptive correlative survey method was used. A questionnaire was designed as a study tool, consisting of (28) items, and divided into five domains. It was distributed to a random stratified sample consisted of (360) teachers of public schools in Kasbah Amman district, and the university in the capital Amman governorate. The results of the study concluded that the degree of public school principals in the capital, Amman, of motivational leadership from the teachers’ point of view, obtained a total average (3.86 out of 5), meaning a (high) degree of practice. Morale with an average of (3.93) and finally the administrative motivation with an average of (3.67), all of them with a degree of practice (high), and that the level of creativity culture among teachers in public schools in the capital Amman, from their point of view, came with a total average (4.16 out of 5), i.e. at a level (high) and at the level of the two areas; The flexibility field got an average of (4.25) with a rating of (very high), then the originality field with an average of (4.08) and the degree of availability (high) for the culture of creativity. Schools for motivational leadership and promoting a culture of creativity among teachers, and based on the results, the researcher recommended the need to encourage school principals to find new motivational strategies and methods that contribute to promoting a culture of creativity among teachers.